Analisis Sifat Elektronik LaFeO3 co-doping Gd dan Co menggunakan Density Functional Theory dengan Generalized Gradient Approximation-Perdew--Burkew--Ernzerhof revised for solids untuk Aplikasi Sensor Gas Aseton - Hendi Haryadi; Edi Suprayoga; Endi Suhendi (Wahana Fisika, 2022)
An analysis of the electronic properties of the LaFeO3 couple doping Gd and Co for acetone gas sensors has been carried out using Density Functional Theory with Generalized Gradient Approximation-Perdew-Burkew-Ernzerhof revised for solids (GGA-PBEsol). Changes in the electronic properties resulting from the adsorption mechanism are discussed here. The simulation results show that the band gap energy for LaFeO3 co-doped Gd and Co before and when exposed to acetone gas molecules are ± 0.501 eV and ± 0.103 eV respectively, with adsorption energy of 0.458 eV. This change in band gap energy indicates that an adsorption-oxidation mechanism has occurred in the system, which is supported by the adsorption energy data. This mechanism is the basic mechanism for gas sensors to work. With this mechanism, LaFeO3 co-doping Gd and Co can be used as candidates for gas sensor applications, especially for acetone gas.